Facile synthesis, characterization, and antimicrobial studies of some disubstituted 1, 2, 3-triazoles with sulfonamide functionality. Issue 16 (18th August 2017) - Kaushik, C. P.; Pahwa, Ashima; Kumar, Ashwani; Singh, Dharmendra; Kumar, Krishan
ABSTRACT: An expedient synthesis of some 1, 4-disubstituted 1, 2, 3-triazoles (3a–3x ) having sulfonamide functionality from various terminal alkynes and aromatic azides through Cu(I)-catalyzed Huisgen 1, 3-dipolar cycloaddition has been reported. The structures of newly synthesized compounds were confirmed by IR, 1 H NMR, 13 C NMR, high-resolution mass spectra and screened for in vitro antimicrobial activity against Staphylococcus aureus (Gram-positive bacteria), Escherichia coli, Klebsiella pneumoniae, Enterobacter aerogenes (Gram-negative bacteria), Candida albicans, and Aspergillus niger (fungi). Some of the synthesized compounds were found to exhibit good potency against above-tested microbial strains. Moreover, to study the binding interactions, docking simulation of broadly active compound3x was also performed against E. coli dihydropteroate synthase enzyme. GRAPHICAL ABSTRACT: